2015
DOI: 10.1007/s10853-015-9163-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of new titanium implants with longitudinal gradient porosity by space-holder technique

Abstract: Bone replacement with conventional biomaterials entails a biomechanical incompatibility with respect to highly specialized and anisotropic bone tissue; stiffness mismatch is the most important example of that event, and it is always present in the components of all prosthetic systems for dental and joint replacements. In the case of titanium implants used for those biomedical applications, the main consequence of that mismatch is the bone resorption around the implants due to stress shielding with respect to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Different studies on titanium implants have shown that at least a 100 µm average pore size is necessary to mark and guide the cellular response to produce and synthetize bone matrix [8,[24][25][26]. Porous titanium parts manufactured with 50% vol.…”
Section: Real Time Monitoring Of Biological Osseointegration and Potementioning
confidence: 99%
“…Different studies on titanium implants have shown that at least a 100 µm average pore size is necessary to mark and guide the cellular response to produce and synthetize bone matrix [8,[24][25][26]. Porous titanium parts manufactured with 50% vol.…”
Section: Real Time Monitoring Of Biological Osseointegration and Potementioning
confidence: 99%
“…The large and irregular pores compromise the fatigue behavior of the implant as well as corrosion resistance, due to porosity [27,28]. However, at least a 100 µm average pore size [26,[29][30][31] is required to guide the cellular response and synthesis bone matrix. This bone in growth through the pores also promotes long term stability and implant osseointegration.…”
Section: Introductionmentioning
confidence: 99%
“…This might be of a great benefit in some biomedical implants such as intramedullary rod or hip stem. [145] Other techniques have also been used to produce porous Ti with a gradient porosity such as the space holder technique [146] and metal injection molding in combination with a space holder. [147] Examples of Biomedical products making use of AM technology are shown in Figure 17 and…”
Section: Biomedical Implantsmentioning
confidence: 99%